2022
DOI: 10.1101/2022.11.30.518628
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying negative selection in human 3’ UTRs uncovers constrained targets of RNA-binding proteins

Abstract: Many non-coding variants associated with phenotypes occur in 3’ untranslated regions (3’ UTRs) and may affect interactions with RNA-binding proteins (RBPs) to regulate post-transcriptional gene expression. However, identifying functional 3’ UTR variants has proven difficult. We used allele frequencies from the Genome Aggregation Database (gnomAD) to identify classes of 3’ UTR variants under strong negative selection in humans. We developed intergenic mutability-adjusted proportion singleton (iMAPS), a generali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…Even though, as mentioned earlier, it has been shown that intergenic variants may be used as an alternative class of variants for the estimation of the baseline level of rare variation (Findlay et al, 2022), we had insufficient evidence that intergenic variants could be used interchangeably with synonymous variants for the purpose of model calibration without any significant effect on the results.…”
Section: Methodsmentioning
confidence: 89%
See 3 more Smart Citations
“…Even though, as mentioned earlier, it has been shown that intergenic variants may be used as an alternative class of variants for the estimation of the baseline level of rare variation (Findlay et al, 2022), we had insufficient evidence that intergenic variants could be used interchangeably with synonymous variants for the purpose of model calibration without any significant effect on the results.…”
Section: Methodsmentioning
confidence: 89%
“…Overall, we believe that our proposed context-based approach is superior compared with using mutability as a proxy for the estimation of the expected level of rare variation, as mutation rates modelling proves a difficult task (Findlay et al, 2022). Even though it is possible to reduce bias of MAPS towards transversion variants by modifying the fit of the model, we argue that this approach can be seen as ad hoc and not future-proof, considering that every new release of gnomAD would require refitting the model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RNA binding protein predictions were generated using the methods detailed in Findlay et al ( 38 ) for all possible variants within motifs that are proximal to ENCODE eCLIP sites, that are also high affinity sites as predicted by RBPamp(39). These were intersected with our variants and filtered to retain only those with a reference affinity of ≥ 0.1 and with an impact of ‘loss of binding’ predicted by the RBP binding affinity model (defined as alternative allele affinity / reference allele affinity < ⅓).…”
Section: Methodsmentioning
confidence: 99%